PENERAPAN SANKSI HUKUM TERHADAP PELANGGARAN KETERBUKAAN YANG DILAKUKAN OLEH EMITEN DI PASAR MODAL INDONESIA - I GUSTI AGUNG WISUDAWAN; BUDI SUTRISNO; DIMAN ADE MULADA; L. ACHMAD FATHONI; ARI RAHMAD HAKIM BF (Universitas Mahasaraswati K. Mataram, 2023)
This study focuses on the application of legal sanctions against disclosure violations committed by issuers in the Indonesian capital market.The type of research used in this research is Normative Research with Statute Approach, Conceptual Approach. This study also uses legal materials which consist of primary legal materials, namely legal materials in the form of Law No. 8 of 1995 concerning Capital Markets and Law No. 21 of 2011 concerning the Financial Services Authority. Secondary Legal Materials, namely literature and scientific articles relating to the issues raised in this study and Tertiary Legal Materials consisting of legal dictionaries and encyclopedias. The technique for collecting legal materials used in this research is a Documentation Study with Analysis of Legal Materials, namely Qualitative Descriptive Analysis. The results of this study are that renewal in the form of reconstruction of legal sanctions in the form of increasing the length of imprisonment and increasing the amount of fines for violations of openness in the Capital Market is absolutely necessary in strengthening the existence of the Capital Market in Indonesia so as to create a healthy economic climate and attract investors to invest in the Indonesian Capital Market. The mechanism for imposing sanctions on issuers who violate transparency in the Capital Market has been regulated normatively in Article 101 of Law No. 8 of 1995 concerning Capital Markets and reaffirmed in Article 9 of Law No. 21 of 2011 concerning the Financial Services Authority and Circular Letters Financial Services Authority of the Republic of Indonesia Number: 7 /SEOJK.04/2022 Concerning Procedures for Examination in the Capital Markets Sector. This is done in order to create substantive justice in the field of the Indonesian Capital Market.